The Sales Model and Brand Building of Lululemon: Key Factors in Market Success - Xu, Ziyao; Ye, Xuening; Zhang, Vicky (Transactions on Economics, Business and Management Research, 2024)
Lululemon, a Canadian brand specializing in yoga apparel, has distinguished itself in the fiercely competitive sportswear market with its unique marketing strategies. This paper provides a comprehensive analysis of Lululemon's current development status from multiple perspectives, including market performance, product innovation, customer demographics, and competitive landscape. The study reveals that Lululemon has built a strong brand influence through precise brand positioning and innovative promotional methods. Additionally, by leveraging grassroots endorsements and effective salesperson techniques, the brand has enhanced its interaction with consumer needs. The unique in-store product mix and brand settings further boost its market competitiveness. Finally, this paper examines the impact of Lululemon's marketing strategies on the marketing environment, covering aspects such as brand loyalty and word-of-mouth marketing, the utilization of digital and social media, and adjustments in competitors' strategies. This study offers valuable insights for the selection and implementation of marketing strategies for sports brands in China.